Caracterização das ascídeas em regiões portuárias do Ceará - Oliveira Filho, Ronaldo Ruy de (2010)
The ascidians are marine benthic invertebrates with worldwide distribution in oceans, occuring from intertidal zones to great depths. The brief planctonic lifetime of ascidians result in a restricted natural dispersion, indicating a potential high endemism. However, in response to the rapid economical development in coastal cities, constructions of harbors and other maritime facilities have favored the introduction of exotic species. In order to establish a baseline for monitoring purposes, a study of the ascidian fauna from Ceara state, northeastern coast of Brazil, was conducted on Pecem Harbor (offshore), as well as on its older counterpart, Mucuripe Harbor (inshore). All collected specimens were identified to the lowest possible taxonomic resolution. As a result, from 38 species found (31 and 30 to Mucuripe and Pecem Harbors, respectively) 16 are new records for the region, and 2 (underlined) were also previously unknown for the Brazilian coast: Ascidia sydneiensis, Ascidia sp.1, Ascidia sp.2, Cnemidocarpa irene, Didemnum cineraceum, Didemnum perlucidum, Didemnum sp., Diplosoma sp., Distaplia bursata, Distaplia sp., Ecteinascidia cf. styeliodes, Eusysntyela sp., Lissoclinum sp., Polyandrocarpa anguinea, Polycarpa tumida e Styela canopus. In spite of the restricted occurrence on harbors, 18 were classified introduced, 9 natives and 7 criptogenic species. The ascidian assemblages were clearly different between harbors (p=0,000), but dominated by two main species: S. canopus and M. exasperatus, even though D. cineraceum and Distaplia sp. were also among the most frequent species observed at Pecem and Mucuripe Harbor, respectively. An increase of species richness was observed in the middle depths (3-4m), with slight decrease for later depth samples. Colonial ascidians were the most representative in richness, but Styelidae was the most important family regarding the number of introduced species. The statistical analysis showed differences between depths (p=0,000), but ascidians assemblages present at Mucuripe Harbor were more clearly stratified, possibly by the influence of external factors such as longer submersion time of pilings and higher turbidity. In conclusion, ascidians are an important group colonizing the pilings at both harbors, but further studies on the harbors and vicinities are need to detect and, if possible, avoid ecological and economical impacts related to invasive ascidians.